2023
DOI: 10.3390/tropicalmed8080386
|View full text |Cite
|
Sign up to set email alerts
|

Tungiasis in the Sanumás Amerindians in the Amazon Rainforest, Brazil: Prevalence, Intensity and Morbidity

Yago Ranniere Teixeira Santana,
Lucas Felipe Carvalho Oliveira,
Gabriela Mafra Lima
et al.

Abstract: Background: Tungiasis is a disease associated with extreme poverty. We aimed to evaluate the prevalence of tungiasis in six different settlements of the Sanumás indigenous community in a remote area in the Auaris region, Yanomami territory, Brazil. Methods: We conducted an observational study to detect clinical and epidemiological factors associated with tungiasis using a cross-sectional strategy and multivariate logistic regression. Soil analysis was performed by visual and microscopic methods. Results: We ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(23 citation statements)
references
References 26 publications
1
22
0
Order By: Relevance
“…A recent survey showed that the point prevalence of tungiasis in this community was 8.11% in January 2022 (95% confidence interval = 6.04-10.78%) [6]. Additionally, the disease mainly affects children in the Sanumás communities and can result in severe secondary complications, including verrucous coccygeal lesions, secondary infection, and deformities (Figure 1) [6]. Moreover, T. penetrans is widely present in the in-house soil of residences, and this is the most important risk factor for the occurrence of tungiasis [6].…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…A recent survey showed that the point prevalence of tungiasis in this community was 8.11% in January 2022 (95% confidence interval = 6.04-10.78%) [6]. Additionally, the disease mainly affects children in the Sanumás communities and can result in severe secondary complications, including verrucous coccygeal lesions, secondary infection, and deformities (Figure 1) [6]. Moreover, T. penetrans is widely present in the in-house soil of residences, and this is the most important risk factor for the occurrence of tungiasis [6].…”
Section: Introductionmentioning
confidence: 88%
“…Control can be difficult in communities where T. penetrans infect humans and animals and where they can be abundantly found in the soil. As a result of this complex environmental interaction, the disease shows epidemic characteristics in some parts of sub-Saharan Africa and South America [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations